2010
DOI: 10.1093/jac/dkq463
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of fluoroquinolone-resistant ST131 Escherichia coli producing CTX-M extended-spectrum  -lactamases in nursing homes in Belfast, UK

Abstract: Gut colonization among nursing home residents in Belfast with ciprofloxacin-resistant E. coli producing ESBLs almost entirely involves clonal spread of ST131 variants, with similar genetic environments for bla(CTX-M-3) or bla(CTX-M-15) as in pEK204 and pEK499. Such diversity indicates dissemination of both plasmids and ESBL genes among a single commonly multiresistant clone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
41
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 22 publications
6
41
1
Order By: Relevance
“…This procedure was also used by Dhanji et al (78) to characterize the plasmids harbored by the fecal CTX-M-15-producing E. coli ST131 isolates detected in stool samples from travelers returning to the United Kingdom from abroad. They showed that 62% of isolates harbored the bla CTX-M-15 genetic environment found in pEK516 and 4.6% harbored the genetic environment found in pEK499, whereas 33% harbored five bla CTX-M-15 genetic environments that had not previously been seen in the United Kingdom.…”
Section: Antibiotic Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…This procedure was also used by Dhanji et al (78) to characterize the plasmids harbored by the fecal CTX-M-15-producing E. coli ST131 isolates detected in stool samples from travelers returning to the United Kingdom from abroad. They showed that 62% of isolates harbored the bla CTX-M-15 genetic environment found in pEK516 and 4.6% harbored the genetic environment found in pEK499, whereas 33% harbored five bla CTX-M-15 genetic environments that had not previously been seen in the United Kingdom.…”
Section: Antibiotic Resistancementioning
confidence: 99%
“…The production of other CTX-M-type enzymes in ST131 E. coli isolates has been documented for CTX-M-1, -2, -3, -9, -10, -14, -18, -24, -27, -28, -32, -39, -52, -55, -65, and 103 (15, 16, 18-20, 22, 29, 32, 45, 60, 71, 74, 83-93). E. coli ST131 isolates producing a number of these enzymes seem to be more frequent in particular countries: ST131 producing CTX-M-14 is particularly common in Canada, China, Japan, and Spain; ST131 producing CTX-M-3 is particularly frequent in the United Kingdom, and ST131 producing CTX-M-27 is common in France, Japan, and Switzerland (18,24,71,74,75,78,84,94). Other non-CTX-M ESBL Ambler class A enzymes have also been described in E. coli ST131 isolates.…”
Section: Antibiotic Resistancementioning
confidence: 99%
“…It is clear, however, that these strains and their multiresistance plasmids have been moving beyond the hospital environment in the United Kingdom for some years (34). A recent study identified ESBLproducing E. coli in the bowel flora of 40% of residents of long-term-care facilities in Belfast; almost half were colonized by strain A (30) and most of the remainder by diverse ST131 variants harboring pEK204-like plasmids (7). The multitude of addiction systems present on pEK499 will, in particular, ensure that it is maintained even in the absence of antibiotic selection.…”
Section: Analysis Of Pek516 (Strain Dmentioning
confidence: 99%
“…The second objective was to assess the association of particular CTX-M enzymes with the clonal background of strains. The third objective was to compare the distribution of the ST131 isolates with that of the non-ST131 isolates with regard to medical wards, clinical samples, and antibiotic susceptibility in order to better understand the epidemiology of this prevalent clone that often produces CTX-M-15 enzymes (1,6,7,11,15,25,26,30). …”
mentioning
confidence: 99%